(untitled) (Research, Society and Development, 2020)
Most of the Pantanal basin, the largest floodplain on the planet, lies in Mato Grosso do Sul state, Midwest Brazil. Located in the center of South America, designated biosphere reserve, the area has long been inhabited, albeit sparsely. Investigating the ways of life of the region’s rural population can shed light on factors associated with quality of life, health status, education, and access to services which, in combination, can provide a balance between rural environment and the goods and services required for inhabiting this landscape. For the first time, a sociodemographic profile of residents of the Paiaguás sub-region of the Pantanal is being reported. These data are feeding a wider investigation of sleep patterns and quality of life of 789 Pantanal residents, to whom a sociodemographic questionnaire was applied collecting information on the following variables: sex; age; educational level; religion; time residing in the region; personal income; household income; daily working hours; marital status, parenthood status, number of children, living arrangement, dwelling ownership, skin color, labor inactivity (retirement), intake of alcohol, coffee, and maté grass infusions, smoking, and engagement in physical activities. Descriptive statistical methods (IBM-SPSS software) were applied to calculate proportions, means, and standard errors of the means for quantitative variables. Significance was defined as p < 0.05 (5%). Most respondents were young, brown, and had little formal education. Most had children, lived with relatives, and were homeowners. Marital status, labor inactivity (retirement), and intake of alcohol, coffee, or maté grass infusions failed to reach significance.